Infinitely Many Solutions for Discrete Boundary Value Problems with the p, q-Laplacian Operator. (27th September 2021) - Zhang, Zhuomin; Zhou, Zhan
Abstract : In this paper, we consider the existence and multiplicity of solutions for a discrete Dirichlet boundary value problem involving the p, q -Laplacian. By using the critical point theory, we obtain the existence of infinitely many solutions under some suitable assumptions on the nonlinear term. Also, by our strong maximum principle, we can obtain the existence of infinitely many positive solutions.